Pengaruh Likuiditas, Leverage, Dan Profitabilitas Terhadap Return Saham Pada Perusahaan Manufaktur Pada Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia - Hartato Rianto; Anita Putri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study was conducted to determine how the influence of the current ratio, debt to equity ratio, and return on assets on stock returns in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange. Data taken from www.idx.co.id. The data used are from 2014 to 2019. The study was conducted in 2021. The population in this study was 61 companies with 39 companies used as samples. This study uses quantitative data that is processed with the Eviews 9 application with the panel regression method. The test results conclude that only the return on assets variable partially has a significant effect on stock returns, while the current ratio and debt to equity ratio partially have no significant effect on stock returns. Simultaneously, the current ratio, debt to equity ratio, and return on assets also have no significant effect on stock returns of manufacturing companies in the basic and chemical industry sectors. The contribution given by the variable current ratio, debt to equity ratio, and return on assets to stock returns is only 1.20%, while the level of closeness of the variables current ratio, debt to equity ratio, and return on assets to stock returns is not very close.